Growth of 100 mm indium antimonide single crystals by modified Czochralski technique - Roman Yu. Kozlov (Pensoft Publishers, 2021)
Currently there is a worldwide trend to increase the diameter of crystals grown from elemental semiconductors and semiconductor compounds. According to literary data the diameter of 3–5 semiconductor single crystals grown nowadays is 4 to 6 inches. So far up to 75 mm indium antimonide single crystals have been grown in Russia. Indium antimonide is the element base for the widest field of solid state electronics, i.e., optoelectronics. Indium antimonide is used for the fabrication of 3–5 mm range linear photodetectors and photodetector arrays used as light-sensitive material in heat vision systems. Growth heat conditions have been selected and 100 mm [100] indium antimonide single crystals have been grown using the modified two-stage Czochralski technique. The graphite heating unit has been oversized to accommodate a 150 mm crucible and a 4.5–5 kg load. The results of the work have provided for a substantial increase in the yield of photodetectors. The electrophysical properties of the as-grown single crystals have been studied using the Van der Pau method and proved to be in agreement with the standard parameters of undoped indium antimonide. Using the 9-field etch method of pit counting under an optical microscope the dislocation density in the 100 mm single crystals has been measured to be ≤ 100 cm-2which is similar to that for 50 mm single crystals.